FAIRLANE, a double-blind placebo-controlled randomized phase II trial of neoadjuvant ipatasertib plus paclitaxel for early triple-negative breast cancer. (30th May 2019) - Oliveira, M; Saura, C; Nuciforo, P; Calvo, I; Andersen, J; Passos-Coelho, J L; Gil Gil, M; Bermejo, B; Patt, D A; Ciruelos, E; de la Peña, L; Xu, N; et al.
Abstract: Background: This hypothesis-generating trial evaluated neoadjuvant ipatasertib–paclitaxel for early triple-negative breast cancer (TNBC). Patients and methods: In this randomized phase II trial, patients with early TNBC (T ≥ 1.5 cm, N0–2) were randomized 1 : 1 to receive weekly paclitaxel 80 mg/m 2 with ipatasertib 400 mg or placebo (days 1–21 every 28 days) for 12 weeks before surgery. Co-primary end points were pathologic complete response (pCR) rate (ypT0/TisN0) in the intention-to-treat (ITT) and immunohistochemistry phosphatase and tensin homolog (PTEN)-low populations. Secondary end points included pCR rate in patients with PIK3CA/AKT1/PTEN -altered tumors and pre-surgery response rates by magnetic resonance imaging (MRI). Results: pCR rates with ipatasertib versus placebo were 17% versus 13%, respectively, in the ITT population ( N = 151), 16% versus 13% in the immunohistochemistry PTEN-low population ( N = 35), and 18% versus 12% in the PIK3CA/AKT1/PTEN -altered subgroup ( N = 62). Rates of overall and complete response (CR) by MRI favored ipatasertib in all three populations (CR rate 39% versus 9% in the PIK3CA/AKT1/PTEN- altered subgroup). Ipatasertib was associated with more grade ≥3 adverse events (32% versus 16% with placebo), especially diarrhea (17% versus 1%). Higher cycle 1 day 8 (C1D8) immune score was significantly associated with better response only in placebo-treated patients. All ipatasertib-treated patients with low immune scores and a CR had PIK3CA/AKT1/PTEN -altered tumors. Conclusions: Adding ipatasertib to 12 weeks of paclitaxel for early TNBC did not clinically or statistically significantly increase pCR rate, although overall response rate by MRI was numerically higher with ipatasertib. The antitumor effect of ipatasertib was most pronounced in biomarker-selected patients. Safety was consistent with prior experience of ipatasertib–paclitaxel. A T-cell-rich environment at C1D8 had a stronger association with improved outcomes in paclitaxel-treated patients than seen for baseline tumor-infiltrating lymphocytes. This dependency may be overcome with the addition of AKT inhibition, especially in patients with PIK3CA/AKT1/PTEN -altered tumors. ClinicalTrials.gov: NCT02301988.